Reservoir Parameter Prediction Based on the Neural Random Forest Model - Wang, Mingchuan; Feng, Dongjun; Li, Donghui; Wang, Jiwei (Frontiers in Earth Science, 2022)
Porosity and saturation are the basis for describing reservoir properties and formation characteristics. The traditional empirical and formulaic methods are unable to accurately capture the non-linear mapping relationship between log data and reservoir physical parameters. To solve this problem, in this study, a novel hybrid model (NRF) combining neural network (NN) and random forest (RF) was proposed based on well logging data to predict the porosity and saturation of shale gas reservoirs. The database includes 6 horizontal wells and the input logs were depth, borehole diameter, neutron, density, gamma-ray and acoustic. The porosity and saturation were chosen as output. The NRF model with independent and joint training was designed to extract key features from well logs data and physical parameters. It provides a promising method for forecasting the porosity and saturation with R2 above 0.93 and 0.77 separately. Compared with baseline models (NN and RF), the NRF model with joint training obtains the unsurpassed performance to predict porosity with R2 above 0.94, which is 1.3% higher than the NRF model with independent training, 4.2% higher than RF, and superior greatly than NN. For the prediction of saturation, the NRF model with joint training still superior to other algorithms with R2 above 0.82, which is 4.7% higher than the NRF model with independent training, 7.4% higher than RF. Furthermore, the NRF model has a similar data distribution with measured porosity and saturation which demonstrates the NRF model can achieve greater stability. It proved that the proposed NRF model can capture the complex relationship of the logging data and physical parameters more accurately and can serve as an economical and reliable alternative tool to give a reliable prediction.